Morphological characterization and nutrient assessment of wild pepper, Piper umbellatum L. (Piperaceae) grown in Sarawak, Malaysia - Saupi, Noorasmah; Lepun, Philip; Alan, Ribka; Zakaria, Muta Harah; Saidin, Ainul Asyira; Yusli, Nurul Aisyah (Update Publishing House, 2021)
Wild pepper, Piper umbellatum L. is traditionally consumed as a leafy vegetable by the indigenous Kenyah tribesmen of Belaga, Sarawak, Malaysia. The shoots are normally harvested from secondary forest floors. The present study was carried out to determine the morphological and nutritional characteristics of P. umbellatum, i.e., proximate, mineral, total phenolic content (TPC), total flavonoid content (TFC), vitamin C, and anti-nutrients, i.e., oxalate and phytate. The results showed that P. umbellatum possesses an ovate, alternate, entire and non-glandular trichome on its leaf surface. The inflorescence comprises an oblongoid spike attached to a peduncle and the ripened berries were orange and red in color. The results also revealed that the leaves of P. umbellatum had a high moisture content (63.27%), other recorded nutrient values were ash (8.62%), crude fiber (19.32%), K (1280.20 mg/100 g), Ca (570.60 mg/100 g), Mg (323.80 mg/100 g) and P (291.14 mg/100 g), TPC (510.63 mg/100 g), TFC (377.82 mg/100 g) and phytate (411.67 mg/100 g). Thus the consumption of the P. umbellatum as a leafy vegetable supplies a good dose of various essential nutrients.